Embedding Ethics in Education: Examining its Role and Importance in Shaping Human Values - Shahzadi, Shazia; Juhary, Ali (2024)
Ethics plays a critical role in all aspects of life, including education, which is a cornerstone of human development. In the context of education, ethics is essential in shaping responsible and morally sound individuals. This paper explores the integration of ethics into the educational system, advocating for its inclusion as a formal part of the curriculum. By incorporating ethics as a dedicated course, students can develop a strong moral foundation, which is vital for personal growth and societal well-being. The discussion will focus on the importance of teaching ethics within educational institutions and its impact on students’ ethical development. Additionally, the concepts of ethics and education will be clearly defined to establish a comprehensive understanding of their interconnectedness. Through this exploration, the paper will highlight the significance of fostering ethical awareness in students to cultivate responsible citizens who can navigate complex moral landscapes in their personal and professional lives.